An Assessment of Complete Denture Changes from Try in to Clinical Insertion- A Retrospective Study - Sai Sandhya.T1 , Mahathi Neralla2 , Suresh Venugopalan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Complete denture is a dental prosthesis that replaces the entire dentition and associated structures of maxillaand mandible. Its Function is to restore esthetics, mastication and speech.Various outcomes in the treatmentof complete denture in edentulous patients involve a complex array of different factors which determine theaccuracy of complete denture. Due to various reasons complete dentures may encounter changes from trialstage to insertion. This change may occur due to processing or handling .The present study aims to assessthe differences in complete denture from try in anterior teeth position to insertion anterior teeth position withregard to midline shift and plane deviation and using chi square test statistical significance was observed.The study was carried out in Saveetha dental college, Chennai, patients data was collected from inhousedigital data bank. The data of documented evidence treated by the undergraduate students were retrieved andanalysed for differences. The study reveals that there are incidences which had changes from the try in stepto clinical insertion step with regard to anterior teeth.